Time course of acclimatization to altitude (2440 m) in female and male runners, and its effects on VO2max and performance - Sucec, A. A.; Hodgdon, J. A.; Roy, B. A.; Hazard, A. A. (Medicine & Science in Sports & Exercise, 1996)
Trained runners (M = 12; F = 7) were measured for VO2max and timed for 1, 2, and 3-mile runs at sea-level and during acclimation to altitude (2,440 m). Observed changes are listed in the table below. The data at altitude were pooled for the genders and expressed as a percentage change from sea-level values. ======================================================================= Measure Time Sex VO2max 1 mile 2 miles 3 miles Sea-level F 54.5 m/kg 5.90 min 12.65 min 19.80 min M 65.3 m/kg 4.81 min 10.44 min 16.49 min Week 1 alt M/F -12.8% 14.3% 11.1% 9.9% Weeks 5/9 alt M/F -9.2% 9.0% 9.6% 7.0% =======================================================================